Sensory Characteristics of Edamame Soy Yogurt with Stevia Sweetener Based on Scoring and Hedonic Tests - Lirista Dyah Ayu Oktafiani; Vadira Rahma Sari; Septi Nur Rachmawati; Nabila Anisa Toyibah; Tasya Cahya Safira (Nusantara Sehat: Jurnal Kesehatan Indonesia, 2026)
Abstract Edamame soy yogurt is a beverage developed from yogurt made from edamame juice. One important aspect in the development of edamame soy yogurt is its sensory characteristics, which are attributes perceived by consumers. The purpose of this study was to determine the sensory characteristics of edamame soy yogurt sweetened with stevia. The research method used was organoleptic testing through scoring and hedonic testing, which included color, aroma, taste, texture, and overall appearance, with panelists selected using purposive sampling consisting of 30 nutrition students as trained panelists. The results of this study indicate that the use of stevia as a substitute for sucrose in edamame soy yogurt does not have a significant difference in organoleptic assessment and hedonic tests for color and aroma. However, there are significant differences in texture characteristics through assessment tests and taste characteristics through hedonic tests. Nevertheless, both organoleptic tests show significant differences in overall acceptance. Keywords: Sensory characteristics, Soy yogurt, Edamame, Stevia